Erro humano ou infração ética: os limites da responsabilização dos profissionais de saúde sob a perspectiva jurídica e da saúde mental - Keyzyhuanda Inácio Bernardes; Oldair Donizete Galeni; Ana Paula de Figueiredo; Eliane Aparecida Peixoto; Neuzilene da Silva Ximenes; Marianina Cerbina Grisi Costa; Francisca Rosilene Mendes; Maria de Fátima Alves; Mariana Paiva Araújo; Jani Kenta Iwata; Monica Martins Moreira Garcez; Sirlene Augusta de Oliveira (Revista ft, 2026)
Healthcare delivery is characterized by high technical complexity, continuous decision-making, and work environments in which human, organizational, and systemic failures may result in incidents and adverse events. However, an undesirable outcome does not automatically imply negligence, recklessness, lack of professional skill, or an ethical violation by the professional involved. This study aims to analyze the limits of healthcare professionals' accountability for errors and adverse events by integrating legal, ethical, patient safety, and mental health perspectives. This is a narrative literature review with a qualitative and descriptive approach, based on scientific articles, Brazilian legislation, professional codes, and institutional documents. The literature demonstrates the need to distinguish unintentional human error, risk-related behavior, and conduct that is effectively negligent or incompatible with professional duties. Indiscriminate blame may strengthen punitive cultures, reduce incident reporting, and increase psychological distress, guilt, anxiety, professional insecurity, and exhaustion among healthcare workers involved in adverse events. In contrast, a just culture seeks to reconcile organizational learning and proportional accountability without eliminating individual responsibility for proven negligent, reckless, unskilled, or intentional conduct. It is concluded that professional accountability should consider individual conduct, foreseeability of harm, specific circumstances, available protocols, working conditions, and systemic factors. Patient protection and healthcare workers' mental health protection are not incompatible objectives but complementary dimensions of safe healthcare systems.